2021
DOI: 10.1039/d1ra02342j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of bisphenol pollutants on imine-based covalent organic frameworks: adsorption behavior and mechanism

Abstract: Two imine-based covalent organic frameworks with different pore sizes were synthesized, and can be used as adsorbents for the removal of bisphenol pollutants, showing high affinity toward bisphenol S and bisphenol A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…As a result, the amount of aromatic that could be adsorbed was reduced. The negative G° indicated that the adsorption was a spontaneous process, and the value of ΔG° decreased as the temperature dropped, showing that lower temperatures enhanced TB and BPA adsorption on FGS2 56 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, the amount of aromatic that could be adsorbed was reduced. The negative G° indicated that the adsorption was a spontaneous process, and the value of ΔG° decreased as the temperature dropped, showing that lower temperatures enhanced TB and BPA adsorption on FGS2 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Between the hydroxyl groups of BPA or TB and the hydrophilic groups (such as carboxyl groups and hydroxyl groups) of FGS2, there are two types of adsorbate-adsorbent interactions: hydrogen bonding and π–π interaction between the benzene ring in BPA and the phenyl groups in FGS2. The adsorption performance of organic pollutants on porous materials like GO/SiO 2 was previously shown to be influenced not only by intrinsic characteristics (e.g., charge, size, and electronic states), but also by weak intermolecular interactions (e.g., hydrogen-bonding and – interactions), hydrophobic interactions, and electrostatic interactions 56 , 57 . The probable adsorption mechanisms involved in TB dye and BPA removal by FGS2 were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research veried that imine COFs with good water stability and abundant C]N binding sites were a good choice for the removal of contaminants from wastewater. [28][29][30] It was reported that the eclipsed honeycomb structure of COF networks formed between 1,3,5-tris(4aminophenyl)benzene (TAPB) and terephthalaldehyde (TPA) by a simple solvothermal approach were highly porous COF precursors, 31,32 and the imine linkages could be easily transformed into amide linkages. 33 These COF networks could, in principle, provide the optimal nano-architecture needed for them to perform well in the extraction of target pollutants.…”
Section: Introductionmentioning
confidence: 99%